Method(s) of error correction in giving feedback to students' written assessment: an investigation on SMA Persekutuan Labu teachers' and students' perceptions / Rohaizan Ahmad - Ahmad, Rohaizan (2012)
The main objective of this study is to examine both students’ and teachers’ perception pertaining to the various methods which are used by the teachers when dealing with students’ written errors. Hence, it was found that the three common methods of error correcting preferred by teachers are underlining, giving comments and using symbols or marking codes which are mostly “indirect feedback”. In contrast, the students tend to favor “direct feedback” especially personal consultation for their error treatment. Thus, there exists a gap and mismatch pertaining to both teachers’ and students’ preferences and needs of error correcting. This gap and mismatch in perceptions and needs should be addressed by all the relevant parties in order to ensure the effectiveness of the method(s) used. Therefore, it is important to note that, teachers play an important role in selecting and providing appropriate corrective feedbacks as this indirectly will influence students’ written performance. In accordance with this, in Malaysian ESL classroom context, students’ perceived that teachers should and needs to correct their written errors as essential platform to develop and further improve their written performance as a whole.